Tourism destination quality : attributes and dimensions - Seakhoa-King, Arthur; Augustyn, Marcjanna M.; Mason, Peter (Bingley, U.K. : Emerald Publishing Limited, 2020)
Tourism Destination Quality: Attributes and Dimensions presents new research on tourism destination quality. It is based on results from the first major empirical study (the TDQ study) that examined what tourists associate with tourism destination quality. It explains why respondents strongly associate attributes and dimensions identified in the TDQ study with destination quality. The book critically compares dimensions of tourism destination quality established in the TDQ study with dimensions of product quality, service quality, place quality and destination service/product quality. To illustrate the applicability and varying importance of dimensions established in the empirical study, case studies of actual tourism destinations are also presented. The empirical evidence provided in this book demonstrates that tourists view destination quality holistically and from the 'quality of opportunity perspective' in terms of conformance to tourists' requirements, which are conditions suitable for pursuing tourist activities and interests. Future directions for research are provided, as well as a diagnostic tool for tourism destination managers and planners. This has been designed to help identify strategic quality improvement areas and to enable competition based on quality in various tourism destination contexts.
Chapter 1: Introduction -- Chapter 2: Approaches To Conceptualising And Measuring Quality -- Chapter 3: Conceptualising And Measuring Quality In Tourism -- Chapter 4: Methodology Of The TDQ Study -- Chapter 5: Findings Of The Qualitative Phase Of The TDQ Study -- Chapter 6: Findings Of The Quantitative Phase Of The TDQ Study -- Chapter 7: Discussion Of The TDQ Study's Findings -- Chapter 8: Conclusions And Recommendations.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Tourism; Tourism -- Quality control; Business & Economics -- Industries -- Hospitality, Travel & Tourism; Tourism industry